Implementasi Manajemen Risiko Keuangan dalam Perusahaan Multinasional: Systematic Literature - Suryono Suryono; Tri Siwi Nugrahani (BISMA : Business and Management Journal, 2025)
This research examines the implementation of financial risk management in multinational corporations through a systematic literature review of 15 selected scientific articles from 2020-2024. The analysis identifies a significant evolution from traditional approaches toward integrated Enterprise Risk Management (ERM) that influences corporate performance. Key findings reveal that ERM implementation effectiveness is influenced by ownership structure, risk committee characteristics, integration of intellectual capital, knowledge management, and digital transformation. Contemporary trends demonstrate convergence between financial risk management and ESG aspects, with digital technology applications accelerating risk identification and mitigation capabilities. The research recommends developing customized risk management approaches, strengthening regulatory frameworks, and accelerating technology adoption in financial risk management for multinational corporations in an era of global uncertainty.